Thinking outside the circle: The Geistkreis and the Viennese "Kreis-Culture" in America - Ohad Reiss-Sorokin (Duke University, Center for the History of Political Economy (CHOPE), 2022)
Besides their ideas and social networks, émigré intellectuals bring with themselves practices for engagement with intellectual work. This article focuses on one such practice: the intellectual Kreis [circle]. It focuses on the Geistkreis, an interwar Viennese interdisciplinary intellectual circle. Based on archival research, the article uses a number of case studies to show that the Kreis was employed by the Viennese emigres as a mental scheme and as a recipe for action. It argues that the émigrés' adherence to the Kreis-structure explains the friction between them and their hosts. By following the attempts of former Geistkreis members to create Kreis-like institutions in America, the article shows that the Kreis was more than mere organizational form. It represented an epistemical commitment to knowledge-making as a collective effort, and the preference of general theoretical knowledge over specialized research. It also entailed an intermingling of 'work' and 'life' that did not conform to American norms.
Keywords: 330; Wissensmanagement; Kollektives Handeln; Migranten; Flüchtlinge; Österreichisch; Geschichte; USA